PENERAPAN METODE KOOPERATIF TIPE STAD DALAM MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SD - Lailan Soviani Soviani; Yufi Latmini Lasari (PGMI Department of Universitas Islam Ibrahimy Banyuwangi, Indonesia, 2023)
Education is an important thing in life of every human. Every human being has the same right t obtain education andd hopes to always develop in eduucation. Through education a person can gain extensive knowledge. In education, it is hope that ther will be change in achievemen and improvement in student learning outcome, especially in social studies learning in elementary school for class V students. So the researc was conducted withthe aim of findingout whether thermwas an increase instudent learning outcome .after implementing the STAD type coperative learning method in social studie learning in elementary schools. This research was carried out because during the research, researchers found a lack of student activity in class and relatively low student larning outcome in social studies subject because teachers when teaching still used the lecture method. Here the researcher uses the Classroom Action Research (PTK) method in the research process. And from theresearch results, it was found thatthere was an increasein student learning outcomes after implementing the STAD type cooperative method. The increase in learning outcome can be see from the comparison between cycle I and cycle II